Prototype Design Of A Food Material Pocket Book With Glycemic Index And Glycemic Load For Diabetes Mellitus Type 2 - Ariq Yusa Firdaus; Edri Indah Yuliza Nur (Poltekkes Kemenkes Tasikmalaya, 2026)
Type 2 Diabetes Mellitus (DMT2) is a chronic metabolic disease with a growing prevalence both globally and nationally. According to the International Diabetes Federation (IDF, 2021), there were 537 million people living with diabetes worldwide, and this number is projected to increase to 643 million by 2030. In Indonesia, the prevalence rose from 1.5% (Riskesdas 2018) to 1.7% in 2023 (SKI 2023). In West Java Province, prevalence increased from 1.28% to 1.7%. In Tasikmalaya City, the number of DM patients reached 635 in 2023, rising from 498 in the previous year. The Indihiang Public Health Center (Puskesmas) area is among the regions with a relatively high number of cases. This study aimed to design a prototype pocket book that provides information on glycemic index (GI) and glycemic load (GL) as an educational medium for individuals with type 2 DM. The research employed a Research and Development (R&D) method using the 4D model (Define, Design, Develop, Disseminate), but was limited to the Develop stage. Validation from subject matter experts yielded a score of 80.1% (valid), while media expert validation achieved 81.7% (very valid), and trial testing with 12 respondents resulted in 89.44% (very good). The pocket book was created using Canva and features clear visuals and accessible language. These results indicate that the pocket book is appropriate for use as an educational tool to help individuals with type 2 DM better understand how to choose suitable foods based on GI and GL.